2016
DOI: 10.1016/j.agee.2016.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Characterising changes in fluorescence properties of dissolved organic matter and links to N cycling in agricultural floodplains

Abstract: A B S T R A C TSand and gravel aquifer systems are common features below and adjacent to river networks and are important in providing a hydrological link between terrestrial and aquatic ecosystems. They are often used for intensive agriculture and therefore provide a conduit for the transport of nutrients to aquatic systems. Understanding the biogeochemical cycles of C and N in such systems is essential in efforts to improve water quality, with a major link being the transfer and properties of DOM which drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…aquifers). Microbial processing of DOM has been shown to alter fluorescence-based indices of DOM composition, with increases in both humification and fluorescence index, indicative of continued microbial decomposition of DOM (Tye and Lapworth, 2016). Given the strong regression observed between lab DOC and DON concentrations and subsequently, between observed and modelled DON we are confident that the load estimation is robust, covering all flow conditions experienced across the period of study.…”
Section: Discussionmentioning
confidence: 69%
“…aquifers). Microbial processing of DOM has been shown to alter fluorescence-based indices of DOM composition, with increases in both humification and fluorescence index, indicative of continued microbial decomposition of DOM (Tye and Lapworth, 2016). Given the strong regression observed between lab DOC and DON concentrations and subsequently, between observed and modelled DON we are confident that the load estimation is robust, covering all flow conditions experienced across the period of study.…”
Section: Discussionmentioning
confidence: 69%
“…In the Penrith Sandstone fluorescence combined with CFCs suggested a rapid flow route to 60 m depth possible fracture flow and increasing recalcitrant fulvic acid content with depth in the rest of the profile. A recent study by Tye and Lapworth (2016) showed higher humification indices in groundwater compared to soils suggesting continued processing of DOM within the aquifer.…”
Section: Organic Carbon Speciation In Groundwatermentioning
confidence: 89%
“…However, more labile protein-like dissolved organic matter (DOM) may also be present in detectable concentrations, particularly where rapid flow pathways in the subsurface are present, from surface sources such as landfills, rivers, urban waste water and agricultural inputs (e.g. Baker and Curry, 2004;Lapworth et al, 2009;Lapworth et al, 2008a;Rhymes et al, 2015;Tye and Lapworth, 2016).…”
Section: Organic Carbon Speciation In Groundwatermentioning
confidence: 99%
“…Inamdar et al [63] found that the DOM fractions in superficial watersheds were composed of humic-like substances, while the DOM fractions from groundwater sources were isolated based on their protein-like fluorescence. Tye and Lapworth [64] revealed that groundwater DOM was generated by the DOM leached from soils in agricultural floodplains. Accordingly, we speculated that the proportions of C-rich organic substances in the soil were increased by N fertilization, mainly owing to the loss of N-rich organic matter via leaching.…”
Section: Water-extractable Organic Matter Composition Is Influenced By Both Carbon and Nitrogen Management Practicesmentioning
confidence: 99%